Establishment of Toxic Metal Reference Range in Tobacco from U.S. Cigarettes - Fresquez, Mark R. (J Anal Toxicol, 2013)
Smoking remains the leading cause of preventable death in the United States. There are numerous harmful substances in tobacco and tobacco smoke. Among the more than 4,000 identified compounds in smoke, many metals contribute to the health risks associated with tobacco use. Specific metals found in tobacco and tobacco smoke have been classified as carcinogens by the IARC. Exposures to toxic metals can cause outcomes including inflammation, sensitization, and carcinogensis. Metals in tobacco are transported in tobacco smoke proportionally with their concentrations in tobacco filler for a given cigarette design. To quantitatively examine metal content in numerous tobacco products, high throughput methods are desired. We developed a simple, rapid tobacco digestion method coupled with a sensitive analytical method using inductively coupled plasma-mass spectrometry (ICP-MS). Because of mercury's known memory effects and volatility, quantitative determinations of mercury were made with a direct combustion analyzer. The methods were utilized to examine arsenic, beryllium, cadmium, chromium, cobalt, lead, manganese, mercury, and nickel content in cigarette tobacco and to establish a reference range for the metals in 50 varieties of cigarettes available in the U.S. Our results are comparable to the limited datasets reported by others and with available standard reference material (SRM) values.